Poverty, inequality, and growth: Trends, policies, and controversies - Ines A. Ferreira; Vincenzo Salvucci; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Reducing poverty and inequality and promoting inclusive growth are fundamental to achieving the United Nations Sustainable Development Goals. Much has changed in the global economy in recent decades and perspectives on progress made vary widely. This is even more so in light of the ongoing COVID-19 pandemic. However, getting to grips in a meaningful manner with existing trends is critical to evidence-based policy-making. This contribution aims to provide an original review and evaluation of the main stylized facts concerning poverty, inequality, and growth. It will uncover existing trends, put controversies into perspective, and help to provide a platform for informed policy debate.
Keywords: D63; I32; O1; 330; poverty; inequality; growth